2019
DOI: 10.1093/nar/gkz929
|View full text |Cite
|
Sign up to set email alerts
|

uS3/Rps3 controls fidelity of translation termination and programmed stop codon readthrough in co-operation with eIF3

Abstract: Ribosome was long considered as a critical yet passive player in protein synthesis. Only recently the role of its basic components, ribosomal RNAs and proteins, in translational control has begun to emerge. Here we examined function of the small ribosomal protein uS3/Rps3, earlier shown to interact with eukaryotic translation initiation factor eIF3, in termination. We identified two residues in consecutive helices occurring in the mRNA entry pore, whose mutations to the opposite charge either reduced (K108E) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…3B) and are important for ribosome maturation and assembly (39,40). Although the uS3-h16 latch has been observed in arrested and terminating ribosomes (41), structural changes in uS3 could also impact initiation and binding to mRNA (SI Appendix, Fig. S7A) (31).…”
Section: Discussionmentioning
confidence: 99%
“…3B) and are important for ribosome maturation and assembly (39,40). Although the uS3-h16 latch has been observed in arrested and terminating ribosomes (41), structural changes in uS3 could also impact initiation and binding to mRNA (SI Appendix, Fig. S7A) (31).…”
Section: Discussionmentioning
confidence: 99%
“…The central region of the RP uS3 (RPS3) contains several conserved basic residues (R116, R117, R146, and K148 in the mammalian protein) that are believed to interact with the mRNA stretch between the entry site and the decoding area [28,[58][59][60]. Residues R116/117 are located at the small subunit close to the mRNA entry pore, and mutation studies with yeasts have demonstrated that they are essential for stabilizing interactions between mRNA and the ribosome at the mRNA entry channel at the stages of the formation of pre-initiation and initiation complexes [58].…”
Section: Conserved Residues Of Rp Us3 (Rps3) At the Binding Site Of T...mentioning
confidence: 99%
“…Binding of eIF3 translation factors to the pre-termination 80S ribosome, likely through interaction with the ribosomal protein uS3/Rps3 (Poncová, Wagner et al 2019), was also shown to interfere with the eRF1-mediated decoding of STOP codons that are set in an unfavorable termination context (Beznosková, Wagner et al 2015). This function is important for re-initiation of mRNAs with uORF and translation of important stress-response protein coding mRNAs such as ATF4 under stress conditions (Hronová, Mohammad et al 2017).…”
Section: Abnormal Translation Termination In Cancermentioning
confidence: 99%